Assessment of a novel device for onsite integrative large-volume solid phase extraction of water samples to enable a comprehensive chemical and effect-based analysis - Schulze, Tobias; Ahel, Marijan; Ahlheim, Jörg; Aït-Aïssa, Selim; Brion, François; Di Paolo, Carolina; Froment, Jean; Hidasi, Anita O; Hollender, Juliane; Hollert, Henner; Hu, Meng; Kloß, Anett; et al. (The Science of the total environment, 2017)
The implementation of targeted and nontargeted chemical screening analysis in combination with in vitro and organism-level bioassays is a prerequisite for a more holistic monitoring of water quality in the future. For chemical analysis, little or no sample enrichment is often sufficient, while bioanalysis often requires larger sample volumes at a certain enrichment factor for conducting comprehensive bioassays on different endpoints or further effect-directed analysis (EDA). To avoid logistic and technical issues related to the storage and transport of large volumes of water, sampling would benefit greatly from onsite extraction. This study presents a novel onsite large volume solid phase extraction (LVSPE) device tailored to fulfill the requirements for the successful effect-based and chemical screening of water resources and complies with available international standards for automated sampling devices. Laboratory recovery experiments using 251 organic compounds in the log D range from -3.6 to 9.4 (at pH7.0) spiked into pristine water resulted in acceptable recoveries and from 60 to 123% for 159 out of 251 substances. Within a European-wide demonstration program, the LVSPE was able to enrich compounds in concentration ranges over three orders of magnitude (1ngL-1 to 2400ngL-1). It was possible to discriminate responsive samples from samples with no or only low effects in a set of six different bioassays (i.e. acetylcholinesterase and algal growth inhibition, androgenicity, estrogenicity, fish embryo toxicity, glucocorticoid activity). The LVSPE thus proved applicable for onsite extraction of sufficient amounts of water to investigate water quality thoroughly by means of chemical analysis and effect-based tools without the common limitations due to small sample volumes.
Keywords: Bioassay analysis; Chemical analysis; Applicability domain; LVSPE; Large-volume solid phase extraction; Effect-based analysis; Automated water sampler